Mitigating the Bridge End Bump Problem: A Case Study of a New Slab System with a Lower Partition Slab-Pile Foundation - Yu Yang; Chuang Yu; Ze-xiang Wu; Dong-mei Tu (Advances in Civil Engineering)
This paper describes a case of using a pile-slab composite foundation to handle a bridge-end bump problem. Conventionally, a deep-seated concrete slab method is employed to tackle this problem; however, this method generates a large stress concentration within 1 m from the bridge end. The mechanical bearing capacity of the deep-seated concrete slab is insufficient and prone to structural damage. Further, the longitudinal slope change rate is also very high. To overcome these limitations and solve the problem, a lower partition slab-pile foundation treatment method is proposed. The construction of the proposed method is provided, and the results of a case study analyzed by field monitoring and a simulation executed using ABAQUS finite element simulation show good agreement. The results indicate that the mechanical bearing characteristics for the proposed lower partition slab-pile foundation treatment method are better than the conventional deep-seated concrete slab method, and therefore, the structure is more resistant to damage. In addition, because the pile foundation enhances the foundation bearing capacity, the longitudinal slope change rate of the new pile-slab composite foundation is 2.5 times that for the deep-seated concrete slab technology. Thus, the lower partition slab-pile foundation treatment method can better deal with the bridge end bump problem.